An industrial quality control study on Chan C. Bros., Incorporated - Acelajado, Carol Anne D. (College of Engineering, 2003)
Chan C. Bros., Inc. is a growing manufacturer of extruded sheets, lighting fixtures, decor lamps, street lighting, park lamps, and acrylic novelty items. Although they have been in the business since 1963, Chan C. Bros, Inc. is unfamiliar with Statistical Process Control. Although the company performs several quality improvement techniques, it is still insufficient to address the quality problems they are experiencing. The main problem of the company, as identified in the Ishikawa Diagram, and as stated by company authorities, is the high percentage of rejection in the extrusion process. This proves to be true since not all extruded sheets are already for delivery; some extruded sheets are transformed to the other product lines using the other production processes of the company. Having a high percentage of rejects in extruded sheets will result to a high failure cost due to either further processing of defective materials or reprocessing/recycling of scraps as raw materials. High rejection rate in the extrusion process is attributable to several defects : color defect, uneven thickness, shrinkage defect, weight variability, unsmooth surface, pinholes, and presence of bank marks, spots, and cracks in the extruded sheets. The causes of these defects are mostly methods and material related. High rejection rate of extruded sheets can be due to improper mixing of raw materials, improper operation of extrusion machine, improper inspection and handling of raw materials, use of contaminated or improperly mixed raw materials, inclusion of rejected scraps in remix, and the use of the wrong dosage of stabilizers and pigments. Other causes of rejected extrudes are discussed in the Problem analysis section of this study. Specifically, the high rejection rate of extrudes is basically due to weight variability caused by the non-attainment of the required range of temperature. After analyzing data points using Control charts, it was found that the extrusion process was out of control. By eliminating variability in the process using SPC tools and after several modifications in the control charts the process was made in control. Other tools used in this study are the Analysis of Variance-used in analyzing variability in the weight measurements; the chi-squared goodness of fit test-used to check the normality of the data points; and the histogram-used in identifying the problem (high percentage of rejected extrudes). As part of the recommended solutions, the group suggests the use of 322-342 degrees Fahrenheit in extruding sheets to minimize, if not totally eliminate weight variability. It is also recommended that the company use Statistical Process Tools as part of their quality improvement techniques to further improve the quality of their products and processes. A similar study should be done on specific product lines and other production processes of the company. Also, all the other causes of high rejection of extruded sheets as mentioned in the Problem Analysis section should be under a similar study. Aside from a Statistical Process Control Study, Chan C. Bros., Inc. could also be subjected under a Methods Engineering Study.